A seroepidemiological investigation on major viral and bacterial pathogens in small-scale chicken flocks in the Mekong delta region of Vietnam - Van, NTB; Van Cuong, N; Nhung, NT; Yen, NTP; Vy, L; Kiet, BT; Van Hoang, N; Hien, VB; Thu, HTV; Chansiripornchai, N; Thwaites, GE; Choisy, M; et al. (Chulalongkorn University Press, 2021)
Small-scale commercial chicken farming represents an important source of income to rural households in the Mekong Delta region of Vietnam. A wide range of vaccines are currently administered to flocks, but is not based on empirical knowledge on pathogen circulation. We collected serum samples and vaccination data from a random sample of 267 small-scale native chicken flocks in Dong Thap to determine serological profiles by ELISA against 8 pathogens: Avian Influenza (AI), Chicken Anaemia virus (CAV), Infectious Bursal Disease (IBD) virus, Infectious Bronchitis virus (IBV), Newcastle Disease virus (NDV), O. rhinotracheale (ORT), P. multocida (PM) and M. gallisepticum (MG). The aims were: (1) to describe the vaccines used; (2) to investigate the relationship between titres and vaccination status; and (3) to identify diseases most likely to be circulating in the area by investigating the seroprevalence in unvaccinated flocks. A total of 33 commercial vaccines against 6 different pathogens had been used, and flocks had been vaccinated against a median of 4 [IQR 3-5] pathogens each. In decreasing order, the highest titres among unvaccinated flocks corresponded to CAV (97.0%), followed by IBD (88.6%), IBV (66.5%), ORT (56.9%), NDV (45.5%), MG (50.9%), AI (21.4%) and PM (2.7%). Given the frequency of clinical cases confirmed in diagnostic laboratory, results support maintaining vaccination programmes against IBD, IBV, NDV and AI. Since MG is commonly detected, inclusion of vaccination against MG is recommended. Ongoing serological monitoring of chicken flock should be carried in conjunction with vaccination data in order to adapt disease control measures to circulating pathogens.